TEACHER PREPARATION: METHODS OF TEACHING MULTIMEDIA TECHNOLOGIES - I.I. Kostykova (Academy of Cognitive and Natural Sciences, 2010)
The problem of foreign language teacher's professional training with multimedia technologies is analyzed in the article.